How Sukuk and Conventional Bond Affect Economic Growth? Evidence from Indonesia - Kartini, Enny; Milawati, Milawati (International Journal of Economics and Financial Issues, 2020)
This study is aimed to show how big the impact of sukuk and conventional bond toward Indonesia's economic growth in the period of 2011-2019 by using ARDL method to observe the impact on the short term and long term. The result of this study shows that on the short term, sukuk does not affect the economic growth and bonds affect the economic growth. As on the long term, sukuk affects the economic growth and bonds do not affect the economic growth. This shows that Indonesian people see sukuk better than conventional bonds in the future. Keywords: Conventional Bond, Growth, Indonesia, Sukuk JEL Classifications: G1, O4, O53 DOI: https://doi.org/10.32479/ijefi.10223